Answer:
6n = 18p
Step-by-step explanation:
Answer: n=3p
Step-by-step explanation:
Evaluate 14 + (-8) ÷ 2 · -3. -9 15 26 -30
For this case we must evaluate the following expression:
14 + (- 8) ÷ 2 * -3
According to the method of algebraic resolution, called PEMDAS, the divisions and multiplications must be made from left to right, before the addition and subtraction, then:
14 + (- 4) * - 3 =
We eliminate the parenthesis keeping in mind that [tex]- * - = +[/tex]
[tex]14 + 12 =[/tex]
Equal signs are added and the same sign is placed:
[tex]14 + 12 = 26[/tex]
Answer:
26
What is the number of terms in this geometric series?
1+2+4...+128
Solve kx - 4 = 9 for x.
Answer:
x = 13/k
Step-by-step explanation:
kx - 4 = 9
Add 4 to each side
kx - 4+4 = 9+4
kx = 13
Divide each side by k
kx/k = 13/k
x = 13/k
Answer:
x = 13/k
Step-by-step explanation:
1) Combine the constants, obtaining:
kx = 13
2) Divide both sides by k to isolate x:
x = 13/k
Which transformation maps trapezoid 2 to trapezoid 6?
Answer:
Clockwise rotation of 90 degrees with the center of rotation being the origin or anti-clockwise rotation of 270 degrees with the center of rotation being the origin.
Step-by-step explanation:
Rotation is one of the examples of linear transformations in which a point or a group of points move at a given angle with the fixed length. This means that the initial points (pre-images) move along the arc of the circle. They can be transformed at any angle. The resultant of any transformation is called the image. The trapezoid 2 is the pre-image and the trapezoid 6 is the image. It can be clearly sensed that the trapezoid 2 is being rotated clockwise at the angle of 90 degrees with the center of rotation being the origin. However, further inspections show that trapezoid 2 can also be mapped/transformed on trapezoid 6 by the anti-clockwise rotation of 270 degrees, center of rotation being the origin. Rest of the trapezoids are either reflections or rotations of different angles!!!
Answer:
Rotation I think.
Which number completes the inequality ?
Answer:
4th option
Step-by-step explanation:
i have answered ur question
Solve the equation (3x-9)+x+(x+28)=184
Final answer:
To solve the equation (3x-9)+x+(x+28)=184, you combine like terms to get 5x + 19 = 184, subtract 19 from both sides to get 5x = 165, and then divide both sides by 5 to find that x = 33.
Explanation:
To solve the equation (3x-9)+x+(x+28)=184, we begin by combining like terms. This involves adding together the x terms and combining the constant numbers. The x terms (3x, x, and x) add up to 5x, and the constants (-9 and +28) add up to 19. Therefore, the equation simplifies to 5x + 19 = 184.
Next, we isolate the variable x. We do this by subtracting 19 from both sides of the equation, getting 5x = 165. Then, we divide both sides by 5 to find x. Dividing 165 by 5, we find that x = 33.
Thus, the solution to the equation is x = 33.
an experiment consists of rolling a six sided die to select a number between 1 and 6 and drawing a card at random from a set of 10 cards numbered 1,2,3 .....10 . Which even definition corresponds to exactly one outcome of the experiment?
So, the event "rolling an even number on the die and drawing an even-numbered card" corresponds to exactly one outcome of the experiment.
In this experiment, there are six possible outcomes from rolling the die (1, 2, 3, 4, 5, or 6) and ten possible outcomes from drawing a card (1, 2, 3, 4, 5, 6, 7, 8, 9, or 10).
To find the total number of outcomes, we multiply the number of outcomes from rolling the die by the number of outcomes from drawing a card: [tex]6 (outcomes from the die) * 10 (outcomes from the card) = 60 possible outcomes.[/tex]
An event corresponds to a specific combination of rolling the die and drawing a card. For example, rolling a 1 on the die and drawing a card numbered 1 is one possible outcome.
Now, let's consider the definition of an event that corresponds to exactly one outcome of the experiment:
An event where the die shows an even number (2, 4, or 6) and the card drawn is also even (2, 4, 6, 8, or 10) would correspond to exactly one outcome of the experiment.
For example, if the die rolls a 2 and the card drawn is a 4, this combination uniquely identifies one outcome of the experiment.
Given the system of equations, what is the y-coordinate of the solution? 5x - 4y = 7 x = 5 - y 36/7 36/23 18/23
Answer:
y=2
Step-by-step explanation:
If I interpreted what you wrote correctly, the equations were 5x-4y=7 and x=5-y. Given these equations, we can substitute the x=5-y into the other equation due to it quite literally being equal to x. When you substitute the x-equation in, it reads 5(5-y)-4y=7. Distribute the 5 into the (5-y) to get 25-5y-4y=7. Combine like terms to get 25-9y=7. Next, subtract the 25 from each side to isolate the -9y. This leaves yoy with -9y= -18. Divide by -9 on each side to isolate and find y. This leaves you with y=2. You can check your work by substituting the y=2 into the second equation to find x and then use the x and y to check your solution in the first equation. :)
Answer:
36/23
Step-by-step explanation:
The graph of this system of equations is which of the following?
2x + y = 6
6x + 3y = 12
Answer:
no solutionStep-by-step explanation:
We only need two points to draw a graph of each equation.
2x + y = 6
Convert to the slope-intercept form y = mx + b:
2x + y = 6 subtract 2x from both sides
y = -2x + 6
for x = 0 → y = -2(0) + 6 = 0 + 6 = 6 → (0, 6)
for x = 3 → y = -2(3) + 6 = -6 + 6 = 0 → (3, 0)
6x + 3y = 12
Convert to the slope-intercept form:
6x + 3y = 12 subtract 6x from both sides
3y = -6x + 12 divide both sides by 3
y = -2x + 4
for x = 0 → y= -2(0) + 4 = 0 + 4 = 4 → (0, 4)
for x = 2 → y = -2(2) + 4 = -4 + 4 = 0 → (2, 0)
Mark given points in the coordinate system.
Draw the lines passing through these points.
Look at the picture.
The lines are parallel. The intersection of the line is not exist. Therefore the system of equations has no solution.
The graph of the given equation is Attached below.
What is the importance of graphs in mathematics?An important math tool is graphing. It can be a straightforward method for introducing more general concepts like most and least, greater than, or less than. It can also be a great way to get your child interested in math and get them excited about it. Using graphs and charts, you can break down a lot of information into easy-to-understand formats that quickly and clearly convey key points.
Given equation 2x + y = 6 we can drive from this equation that at x = 0 y will be 6 and y =0 x will be 3 hence we have two points of the line (0,6) and (3,0)
From the Given equation (2) 6X + 3Y = 12 we can drive from this equation that at x = 0 y will be 4 and y =0 x will be 2 hence we have two points of the line (0,4) and (2,0).
Hence, we have two coordinates from both lines which is enough to draw a line on an XY cartesian plan.
Learn more about graphs here:
https://brainly.com/question/17267403
#SPJ5
4/5 of a class is girls and there are 8 boys. How many total in class.
Answer:
40
Step-by-step explanation:
a+b=c
a=girls
b= boys
c= total
the statement tell us:
4/5 of a class is girls:
a=(4/5)*c
boys=b=8
c=a+b
so we have:
c=(4/5)*c + 8
c-(4/5)*c=8
(5c-4c)/5 = 8
c/5=8
c=8*5
c=40
total=40
How to solve question 20? Please help!!
Answer:
E. 36 is the answer.
Step-by-step explanation:
27 is a multiple of 9. 9 is 1/3 of 27. Add 9 with 27 to get 36. 9/36 is equal to 1/4. To prove it, multiply 9 with 4 to get 36.
I hope this was clear!
Determine if this graph is an example of function..
A graph is a function if it passes the vertical line test. The vertical line test is where you take a vertical (up and down) line and test all spots of the graph. If the graph intersects the vertical line more then once then it is not a function, it is a relation. If the vertical line only crosses the graph once then it is a function.
Look at the image below to see the vertical line test for this graph:
The vertical line crosses the graph twice, therefore this is not a function. It is a relation.
Hope this helped!
~Just a girl in love with Shawn Mendes
Identify the asymptotes of
Answer:
x=-1 vertical
y=4 horizontal
Step-by-step explanation:
The vertical asymptote if it exist will be the x's such that it makes your fraction undefined. You cannot divide by 0. So 2/(x+1) will be undefined when x=-1.
x=-1 is your vertical asymptote.
Now a fraction will only be 0 when the top is 0. 2/(x+1) will therefore never be 0 because the numerator will never be 0.
So since 2/(x+1) is never 0, you have 2/(x+1) + 4 is never 4.
So the horizontal asymptote is y=4.
which shows the root(s) of y^2-12y=-36?
a. 6 and -6
b. 6 only
c. 36 and 1
d. -6 only
The answer is 6 only.
The roots of the equation y^2 - 12y = -36 can be found by rewriting the equation as y^2 - 12y + 36 = 0 to make it quadratic.
By factoring this quadratic equation, we get (y - 6)(y - 6) = 0, resulting in one repeated root at y = 6.
Therefore, the correct answer is b. 6 only.
4b - 2 =6
Show step by step how to solve and check (giving 10 points)
Answer:
b=2
Step-by-step explanation:
1.1 Pull out like factors :
4b - 8 = 4 • (b - 2)
Equation at the end of step 1 :
Step 2 :
Equations which are never true :
2.1 Solve : 4 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
2.2 Solve : b-2 = 0
Add 2 to both sides of the equation :
b = 2
One solution was found :
b = 2
Answer:
b = 2
Step-by-step explanation:
Equation: 4b - 2 = 6
Step 1: Use the addition property of equality by adding 2 on both sides to put x on one side. Now we have the equation 4b = 8.
Step 2: Use the division property of equality by dividing 4 on both sides to isolate x. Now we have the equation b = 2.
Step 3: Verify your answer by substituting 2 into the equation 4b - 2 = 6. Now we have 4(2) - 2 = 6, which is the same as 8 - 2 = 6. After simplifying, we get 6 = 6, which is a true statement. Therefore, the answer is b = 2
Write an equation of the line passing through the point (-8, -4) that is perpendicular to the line given by y= 1/6 x+3.
Answer:
y+4=-6(x+8) point-slope form
y=-6x-52 slope-intercept form
6x+y=-52 standard form
Step-by-step explanation:
Slope-intercept form of a line is y=mx+b where m is the slope and b is the y-intercept.
Lines that are perpendicular have opposite reciprocal slopes.
So the slope of y=(1/6)x+3 is 1/6.
The opposite reciprocal of (1/6) is -6.
So the equation for the line we are looking for is in the form:
y=-6x+b (Since the slope of our new line is -6)
Now we want our line to go through (-8,-4).
So plug that in:
-4=-6(-8)+b
-4=48+b
Subtract 48 on both sides:
-52=b
The equation for the line we are looking for is
y=-6x-52.
Now you could do other forms.
Another one is point-slope form.
We already know it goes through (-8,-4) and a slope of -6.
Point slope form is: y-y1=m(x-x1) where m is the slope and (x1,y1) is a point on the line.
Plug in the information to get:
y-(-4)=-6(x-(-8))
y+4=-6(x+8)
I'm going to do one more form.
Standard form is ax+by=c where a,b,c are integers.
y=-6x-52
Add 6x on both sides:
6x+y=-52
What is the recursive formula for this geometric sequence?
-3, -21, -147, -1029, ...
[tex]a_1=-3\\r=7\\a_n=a_{n-1}\cdot r\\\\ \boxed{a_n=7a_{n-1}}[/tex]
[tex]a_{n+1} =7a_{n}[/tex].
If we know the term [tex]n^{th}[/tex] and the common relation, r, of a geometric sequence, you can find the term [tex](n+1)^{th}[/tex] using the recursive formula [tex]a_{n+1} =a_{n}.r[/tex].
The first term of the geometric sequence is a₁ = -3.
The common relation we have to find the relationship between a term and the term that precedes it.
[tex]r=\frac{-21}{-3} = 7[/tex]
The recursive formula is:
[tex]a_{1} =-3[/tex]
[tex]a_{n+1} =7a_{n}[/tex]
given the center of the circle (-3,4) and a point on the circle (-6,2), (10,4) is on the circle
true or false
given the center of the circle (1,3) and a point on the circle (2,6), (11,5) is on the circle
true or false
Answer:
Part 1) False
Part 2) False
Step-by-step explanation:
we know that
The equation of the circle in standard form is equal to
[tex](x-h)^{2} +(y-k)^{2}=r^{2}[/tex]
where
(h,k) is the center and r is the radius
In this problem the distance between the center and a point on the circle is equal to the radius
The formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
Part 1) given the center of the circle (-3,4) and a point on the circle (-6,2), (10,4) is on the circle.
true or false
substitute the center of the circle in the equation in standard form
[tex](x+3)^{2} +(y-4)^{2}=r^{2}[/tex]
Find the distance (radius) between the center (-3,4) and (-6,2)
substitute in the formula of distance
[tex]r=\sqrt{(2-4)^{2}+(-6+3)^{2}}[/tex]
[tex]r=\sqrt{(-2)^{2}+(-3)^{2}}[/tex]
[tex]r=\sqrt{13}\ units[/tex]
The equation of the circle is equal to
[tex](x+3)^{2} +(y-4)^{2}=(\sqrt{13}){2}[/tex]
[tex](x+3)^{2} +(y-4)^{2}=13[/tex]
Verify if the point (10,4) is on the circle
we know that
If a ordered pair is on the circle, then the ordered pair must satisfy the equation of the circle
For x=10,y=4
substitute
[tex](10+3)^{2} +(4-4)^{2}=13[/tex]
[tex](13)^{2} +(0)^{2}=13[/tex]
[tex]169=13[/tex] -----> is not true
therefore
The point is not on the circle
The statement is false
Part 2) given the center of the circle (1,3) and a point on the circle (2,6), (11,5) is on the circle.
true or false
substitute the center of the circle in the equation in standard form
[tex](x-1)^{2} +(y-3)^{2}=r^{2}[/tex]
Find the distance (radius) between the center (1,3) and (2,6)
substitute in the formula of distance
[tex]r=\sqrt{(6-3)^{2}+(2-1)^{2}}[/tex]
[tex]r=\sqrt{(3)^{2}+(1)^{2}}[/tex]
[tex]r=\sqrt{10}\ units[/tex]
The equation of the circle is equal to
[tex](x-1)^{2} +(y-3)^{2}=(\sqrt{10}){2}[/tex]
[tex](x-1)^{2} +(y-3)^{2}=10[/tex]
Verify if the point (11,5) is on the circle
we know that
If a ordered pair is on the circle, then the ordered pair must satisfy the equation of the circle
For x=11,y=5
substitute
[tex](11-1)^{2} +(5-3)^{2}=10[/tex]
[tex](10)^{2} +(2)^{2}=10[/tex]
[tex]104=10[/tex] -----> is not true
therefore
The point is not on the circle
The statement is false
Bo is buying a board game that usually costs B dollars. The game is on sale and the price has been reduced by
18
Which of the following expressions could represent how much Bo pays for the game?
Choose 2 answers
Answer:
B - 0.18B
0.82B
Step-by-step explanation:
If B is the price of the board game, then the discount will be:
B * 18/100
= B * 0.18
= 0.18B
The expression for the cost Bo will pay for the game is:
B - 0.18B => Original price - discount
The expression can also be written as: (after solving)
0.82B ..
Answer:
A=0.82B
E=B−0.18B
hope this helps
A 150-pound person will burn
100 calories while sitting still for
1 hour. Using this ratio, how many
calories will a 100-pound person
burn while sitting still for 1 hour?
A. 666 2/3 calories
B. 66 2/3calories
C. 6 2/3 calories
Answer:
B
Step-by-step explanation:
150/100=2/3
2/3 of 100 = 66 2/3
A 100-pound person will burn 66 2/3 calories while sitting still for 1 hour.
Explanation:To find out how many calories a 100-pound person will burn while sitting still for 1 hour, we can use the given ratio of 150-pound person: 100 calories = 1 hour. Since the ratio is constant, we can set up a proportion to solve for the unknown value:
150 pounds : 100 calories = 100 pounds : x calories
Coss-multiplying, we get:
150 pounds * x calories = 100 pounds * 100 calories
Simplifying, we have:
x = (100 pounds * 100 calories) / 150 pounds
Calculating the value of x, we find that a 100-pound person will burn 66 2/3 calories while sitting still for 1 hour.
https://brainly.com/question/22374134
#SPJ12
Which Function has the graph below?
Answer:
C
Step-by-step explanation:
The general rule for the quadratic function is
[tex]y=ax^2+bx+c[/tex]
From the graph you can see that the curve passes through the points (2,4), (1,7) and (3,7), so
[tex]y(2)=4\Rightarrow 4=a\cdot 2^2+b\cdot 2+c\\ \\y(1)=7\Rightarrow 7=a\cdot 1^2+b\cdot 1+c\\ \\y(3)=7\Rightarrow 7=a\cdot 3^2+b\cdot 3+c[/tex]
We get the system of three equations:
[tex]\left\{\begin{array}{l}4a+2b+c=4\\ \\a+b+c=7\\ \\9a+3b+c=7\end{array}\right.[/tex]
Subtract these equations:
[tex]\left\{\begin{array}{l}4a+2b+c-a-b-c=4-7\\ \\9a+3b+c-a-b-c=7-7\end{array}\right.\Rightarrow \left\{\begin{array}{l}3a+b=-3\\ \\8a+2b=0\end{array}\right.[/tex]
From the second equation:
[tex]b=-4a[/tex]
Substitute it into the first equation:
[tex]3a-4a=-3\\ \\a=3[/tex]
So,
[tex]b=-4\cdot 3=-12[/tex]
and
[tex]3+(-12)+c=7\\ \\c=7+9=16[/tex]
The quadratic function is
[tex]y=3\cdot x^2-12x+16[/tex]
Sara wanted to gather data about the cost of local gyms in her area. She plotted the data and determined that the average gym costs consist of a one-time registration fee and a monthly fee modeled by the equation y = 10x + 30.
Identify and interpret the y-intercept in this model.
a. The y-intercept is 30. This is the cost of registration.
b. The y-intercept is 30. This is the cost per month.
c. The y-intercept is 10. This is the cost of registration.
d. The y-intercept is 10. This is the cost per month.
[tex]\bf y = \stackrel{\stackrel{monthly~fee}{\downarrow} }{10}~~\stackrel{\stackrel{month}{\downarrow }}{x}+\underset{y-intercept}{\stackrel{\stackrel{registration~fee}{\downarrow }}{30}}~\hfill \impliedby \begin{array}{|c|ll} \cline{1-1} slope-intercept~form\\ \cline{1-1} \\ y=\underset{y-intercept}{\stackrel{slope\qquad }{\stackrel{\downarrow }{m}x+\underset{\uparrow }{b}}} \\\\ \cline{1-1} \end{array}[/tex]
Answer: a. The y-intercept is 30. This is the cost of registration.
Step-by-step explanation:
The standard equation of line in intercept form is given by :-
[tex]y=mx+c\ \ \ \ \ \ \ (i)[/tex], where m is the slope of the line and c is the y-intercept.
Given : Sara plotted the data and determined that the average gym costs consist of a one-time registration fee and a monthly fee modeled by the equation :-
[tex]y = 10x + 30[/tex]
By comparing it to the equation (i), we have
c=30 and m=10
i.e. The y-intercept is 30.
Also, y-intercept of any function shows the starting value of the function when x=0.
Thus, This is the cost of registration ( starting fee).
What is the solution to the system?
-2x + y + 6z = 1
3x + 2y + 5z = 16
7x + 3y – 4z = 11
Final answer:
To solve the system of equations, use the method of substitution to find the values of x, y, and z.
Explanation:
To find the solution to the system, we can use the method of elimination or substitution. Let's use the method of substitution to solve this system.
From the first equation, we can isolate y in terms of x and z: y = 2x + 6z - 1.
Substitute this expression for y in the other two equations to eliminate the variable y. This will give you an equation with variables x and z.
Solve the resulting equation to find the values of x and z.
Substitute these values back into any of the original equations to solve for the remaining variable, y.
The solution to the system -2x + y + 6z = 1, 3x + 2y + 5z = 16, and 7x + 3y - 4z = 11 is x = 1, y = 2, and z = 3.
One solution of 21x^2 + bx -4 = 0 is -4/3. Find b and the other solution.
Answer:
see explanation
Step-by-step explanation:
Given that x = - [tex]\frac{4}{3}[/tex] is a solution of the equation, then
Substitute this value into the equation and solve for b
21 (- [tex]\frac{4}{3}[/tex] )² + b (- [tex]\frac{4}{3}[/tex] ) - 4 = 0
21 × [tex]\frac{16}{9}[/tex] - [tex]\frac{4}{3}[/tex] b - 4 = 0
[tex]\frac{112}{3}[/tex] - [tex]\frac{4}{3}[/tex] b - 4 = 0
Multiply through by 3
112 - 4b - 12 = 0
100 - 4b = 0 ( subtract 100 from both sides )
- 4b = - 100 ( divide both sides by - 4 )
b = 25 ← value of b
The equation can now be written as
21x² + 25x - 4 = 0 ← in standard form
with a = 21, b = 25, c = - 4
Use the quadratic formula to solve for x
x = ( - 25 ± [tex]\sqrt{25^2-(4(21)(-4)}[/tex] ) / 42
= ( - 25 ± [tex]\sqrt{961}[/tex] ) / 42
= ( - 25 ± 31 ) / 42
x = [tex]\frac{-25-31}{42}[/tex] = [tex]\frac{-56}{42}[/tex] = - [tex]\frac{4}{3}[/tex]
or x = [tex]\frac{-25+31}{42}[/tex] = [tex]\frac{6}{42}[/tex] = [tex]\frac{1}{7}[/tex]
The other solution is x = [tex]\frac{1}{7}[/tex]
Solve for x in the picture please
Answer:
The value of x is 4
Step-by-step explanation:
we know that
The Intersecting Secants Theorem states that When two secant lines intersect each other outside a circle, the products of their segments are equal
so
[tex](x-1+5)(5)=(x+2+4)(4)\\ (x+4)5=(x+6)4\\5x+20=4x+24\\5x-4x=24-20\\x=4[/tex]
In May you used 600 kilowatts-hours of energy for electricity. Calculate your average power use in watts.
Answer:
The average power use in watts is 806.
Step-by-step explanation:
The month of May has 31 days and 1 day is 24 hours. So May has:
31*24=744 hours
Now, we divide 600 kW-hr by the number of hours in the month (744 hrs) to get average power use:
600/744 = 0.80645161. kW. Since 1000 Watts = 1 kW, we multiply this by 1000 to get the answer in Watts:
0.80645161 * 1000 = 806 Watts
"The average power use is 806 watts."
Identify the explicit function for the sequence in the table.
Answer:
B
Step-by-step explanation:
The sequence is as follows:
7,19,31,43,55
Here:
a_1=7
d= 12
The standard formula for arithmetic sequence is:
[tex]a_n=a_1+(n-1)d\\a_n=7+(n-1)12[/tex]
By looking at the options we can see that
option B is correct ..
Answer: B a(n)=7+(n-1)*12
Step-by-step explanation:
A P E X
A'B'C'D' is the image of ABCD. What transformation(s) would result in this image?
Answer:
An anti-clockwise rotation of 180 degrees about the origin.
Step-by-step explanation:
We can draw a straight line between A and A' going through (0, 0). Same with the other points. We also see that A'B'C'D' faces the opposite way to ABCD which is characteristic of a rotation of 180 degrees.
This design shows several circles with the same center. The total radius of the design is 8 inches. The angle shown has a measure of 30°. The shaded section of the outermost ring has a side length of 2 in. What is the perimeter of the shaded portion? Express the answer as a decimal rounded to the nearest hundredth.
Answer:
11.33 in. to the nearest hundredth.
Step-by-step explanation:
The perimeter of the shaded area = length of the 2 straight lines + the length of the 2 arcs = 4 + length of the 2 arcs.
Calculate the length of the outer arc:
This equals (30 / 360) * perimeter of the largest circle
= 1/12 * 2 π * 8
= 4/3 π in.
The inner circle has a radius of 8 - 2 = 6 ins
so the length of the inner arc
= 1/12 * π * 2 * 6
= π in.
So the perimeter of the shaded region = 4 + 4/3 π + π
= 4 + 7π/3
= 11.33 in.
Which triangle is congruent to ACAT by the ASA Postulate?
AINE
ADOG
AGDO
AFNI
Triangle GDO is the correct answer.
Although Triangle DOG seems like the exact same triangle, it's not (Ok, well technically it is, but when showing two congruent triangles, the points on the triangle should correspond to eachother).